Possible erythropoietin pharmacotherapeutic targets on painful diabetic neuropathy in rats - SAMUEL SUAREZ-MENDEZ; DEYSI Y. BERMÚDEZ-OCAÑA (Anais da Academia Brasileira de Ciências)
Abstract Erythropoietin is a renal cytokine involved in regulating hematopoiesis. Current evidence indicates that erythropoietin exerts pleiotropic effects in animal models. However, its role in painful diabetic neuropathy, as well as the possible action mechanisms are not yet established. Therefore, this was the purpose of our study. Rats were injected with streptozotocin to produce hyperglycemia. The mechanical allodynia was measured by the up-down method using the von Frey filaments in diabetic rats. To determine the action mechanisms of erythropoietin, levels of NF-κB in serum were measured with ELISA and was used L-NAME (Nω-nitro-L-arginine methyl ester hydrochloride, non-selective nitric oxide synthase inhibitor; 0.1-1 mg/kg, i.p.), glibenclamide (ATP-sensitive K+ channels blocker; 1-10 mg/kg, i.p.), methiothepin (non-selective 5-HT receptor antagonist; 0.01-0.1 mg/kg, i.p.) and naloxone (non-selective opioid receptor antagonist; 1 mg/kg). Intraperitoneal administration of erythropoietin (500-4000 UI/kg) prevented allodynia in diabetic rats. Additionally, erythropoietin significantly decreased serum levels of NF-κB during the evaluation of tactile allodynia and L-NAME, glibenclamide and methiothepin, but not naloxone, reverted erythropoietin-induced antiallodynia. These data suggest erythropoietin effect on painful diabetic neuropathy are mediated at least in part, via deactivation of NF-κB, activation of nitric oxide-ATP-sensitive K+ channel pathway as well as the activation of 5-HT receptors.